The accuracy of four formulas for LDL-C calculation at the fasting and postprandial states - Xu, Jin; Du, Xiao; Zhang, Shilan; Xiang, Qunyan; Zhu, Liyuan; Liu, Ling (Frontiers in Cardiovascular Medicine, 2022)
Background Elevated level of low-density lipoprotein cholesterol (LDL-C) is concerned as one of the main risk factors of cardiovascular disease, at both fasting and postprandial states. This study aimed to compare measured LDL-C with LDL-C calculated by the Friedewald, Martin/Hopkins, Vujovic, and Sampson formulas, and establish which formula could provide the most reliable LDL-C results for Chinese subjects, especially at the postprandial state. Methods Twenty-six subjects were enrolled in this study. The blood samples were collected in all subjects before and after taking a daily breakfast. The calculated LDL-C results were compared with LDL-C measured by vertical auto profile method, at both fasting and postprandial states. The percentage difference between calculated and measured LDL-C (total error) and the number of results exceeding the total error goal of 12% were established. Results The calculated LDL-CF levels showed no significant difference to LDL-CVAP levels at the fasting state. The calculated LDL-CS were significantly higher than LDL-CVAP at the fasting state(P < 0.05), while were very close to LDL-CVAP levels after a daily meal. At the fasting state, the median total error of calculated LDL-CF was 0(quartile: -3.8 to 6.0), followed by LDL-CS, LDL-CMH and LDL-CV. At the postprandial states, the median total errors of LDL-CS were smallest, 1.0(-7.5,8.5) and -0.3(-10.1,10.9) at 2 h and 4 h, respectively. The calculated LDL-CF levels showed the highest correlation to LDL-CVAP and accuracy evaluating fasting LDL-C levels, while Sampson formula showed the highest accuracy at the postprandial state. Conclusion The Friedewald formula was recommended to calculate fasting LDL-C, while Sampson formula seemed to be a better choice to calculate postprandial LDL-C levels in Chinese.